Pharmacokinetics, pharmacodynamics, and safety of apixaban in subjects with end‐stage renal disease on hemodialysis. (22nd December 2015) - Wang, Xiaoli; Tirucherai, Giridhar; Marbury, Thomas C.; Wang, Jessie; Chang, Ming; Zhang, Donglu; Song, Yan; Pursley, Janice; Boyd, Rebecca A.; Frost, Charles
Abstract: An open‐label, parallel‐group, single‐dose study was conducted to assess the pharmacokinetics, pharmacodynamics, and safety of apixaban in 8 subjects with end‐stage renal disease (ESRD) on hemodialysis compared with 8 subjects with normal renal function. A single oral 5‐mg dose of apixaban was administered once to healthy subjects and twice to subjects with ESRD, separated by ≥7 days: 2 hours before (on hemodialysis) and immediately after a 4‐hour hemodialysis session (off hemodialysis). Blood samples were collected for determination of apixaban pharmacokinetic parameters, measures of clotting (prothrombin time, international normalized ratio, activated partial thromboplastin time), and anti‐factor Xa (FXa) activity. Compared with healthy subjects, apixaban Cmax and AUCinf were 10% lower and 36% higher, respectively, in subjects with ESRD off hemodialysis. Hemodialysis in subjects with ESRD was associated with reductions in apixaban Cmax and AUCinf of 13% and 14%, respectively. The percent change from baseline in clotting measures was similar in healthy subjects and subjects with ESRD, and differences in anti‐FXa activity were similar to differences in apixaban concentration. A single 5‐mg oral dose of apixaban was well tolerated in both groups. In conclusion, ESRD resulted in a modest increase (36%) in apixaban AUC and no increase in Cmax, and hemodialysis had a limited impact on apixaban clearance.